2013
DOI: 10.9734/ajea/2013/2030
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Agricultural Productivity among Arable Crop Farmers in Imo State, Nigeria

Abstract: The main objectives of the study were to examine and identify the factors that affect agricultural productivity in Imo State, Nigeria. The method of proportionate random sampling technique was used in selecting a sample of 99 farmers who were interviewed using validated, structured questionnaire. Primary data collected were analyzed using frequencies, means, and the Ordinary Least Squares multiple regression analysis technique. The results of the analysis show that the marginal value products estimated for far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
19
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 8 publications
10
19
5
Order By: Relevance
“…This means that output of male farmers was 23.3% better than their female counterparts. The results from Table (3) also revealed that a 100% increase in farm size resulted in a 10.8% increase in output, corroborating with Ajah and Nmadu (2012) and Obasi et al (2013) that an increase in area of farm land cultivated resulted in an increase in crop output.…”
Section: Determinants Of Rice Output Among Farmerssupporting
confidence: 80%
“…This means that output of male farmers was 23.3% better than their female counterparts. The results from Table (3) also revealed that a 100% increase in farm size resulted in a 10.8% increase in output, corroborating with Ajah and Nmadu (2012) and Obasi et al (2013) that an increase in area of farm land cultivated resulted in an increase in crop output.…”
Section: Determinants Of Rice Output Among Farmerssupporting
confidence: 80%
“…Eleven respondents (or 11.5%) did not fall into that category. The proportion compared favourably with the 82.0% and 83.8% of married farmers in other studies by Ibitoye and Onimisi (2013) and Obasi et al (2013), respectively. The analysis of respondents by whether they were full-time or part-time cassava farmers showed that only 32.29% was into cassava farming fulltime (Fig.…”
Section: Fig 4 Farmers Exposed To Farm Management Trainingmentioning
confidence: 41%
“…β k X k + ei …………………………………….eq(2) Where: α = intercept Y = Farmers output (in kg).  1 - 10 =Regression coefficient ei = Error term designed to capture the effects of unspecified variables in the model X 1 = Urbanization (weighted mean of responses) X 2 = Pollution (weighted mean of responses) X 3 = Erosion (weighted mean of responses) X 4 = Flooding (weighted mean of responses) X 5 = Limited farm land (weighted mean of responses) X 6 = Land tenure (weighted mean of responses) X 7 = Rainfall (weighted mean of responses) X 8 = Temperature (weighted mean of responses) X 9 = Fire (weighted mean of responses) X 10 = Grazers (weighted mean of responses)  = Constant term The α and β S are the parameters for estimation and these are the error terms s.…”
Section: Methods Of Data Analysismentioning
confidence: 99%